PEMBELAJARAN INOVATIF DI SEKOLAH DASAR BERDASARKAN PARADIGMA TEORI BELAJAR HUMANISTIK - Ilahi, Rahmat; Jeva Mareski (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study endeavors to delineate the principles of humanistic learning theory as applied to the implementation of novel pedagogical approaches in primary education. The methodology employed herein is that of a literature review, with data procured from a diverse array of resources, including physical libraries and various online platforms.The selected materials encompass books, encyclopedias, dictionaries, scholarly journals, official documents, periodicals, and other relevant publications. Data collection was accomplished through the utilization of documentary techniques. Subsequently, content analysis was applied as the method for data scrutiny. The findings of this investigation suggest that innovative learning constitutes an educational framework developed by educators through novel methodologies. This innovative design aims to assist students in constructing knowledge and facilitating behavioral modification. Humanistic learning theory serves to enhance students' engagement with subject matter, thereby fostering the development of their inherent capabilities towards improvement. Consequently, humanistic learning theory is applicable to the execution of innovative learning strategies within elementary school settings. This theory underscores the significance of guided instruction, cultivating and directing students' fundamental potential across cognitive, affective, and psychomotor domains.